Determination of the gallbladder wall thickness in patients with cholecystitis and cholelithiasis by ultrasonography in North Indian population - Vishram Singh; Durgesh Singh; Ashutosh Tandon; Yogesh Yadav; Richa Tiwari (Acta Medica International, 2019)
Objective: The objective of the study was to determine the gallbladder (GB) wall thickness in patients with cholecystitis and cholelithiasis with the help of ultrasonography in North Indian population for the estimation of epidemiology. Aim: The aim was to estimate epidemiology of the GB wall thickness in patients with cholecystitis and cholelithiasis by ultrasonography in North Indian population. Materials and Methods: This was a hospital-based case–control study. Patients with cholecystitis and cholelithiasis of age between 15 and 70 years of either sex were included in the study. The GB wall thickness was determined in the fasting state. A total of 50 samples, 36 cases (with diseased bladder) and 14 controls (with normal bladder) were included in the study. Results: More than one-third of cases (38.9%) were between 30 and 40 years. The mean age of cases and controls was 42.22 ± 12.81 and 35.43 ± 11.85 years, respectively. More than one-third of both cases (36.1%) and controls (35.7%) were males. The GB wall thickness was significantly (P = 0.005) higher among the cases (4.06 ± 2.28 mm) than that of controls (2.22 ± 0.67 mm). Full distention of the GB was in more than half of both cases (69.4%) and controls (57.1%). Partial distended was in 11.1% of cases and in 21.4% of controls. Contracted (8.3%) and overdistended (2.8%) were only seen among cases. The GB wall thickness of ≥3 mm was among 66.7% of patients and in 14.3% of controls. The GB wall thickness of <3 mm was 92% lower in cases compared to controls (odds ratio = 0.08, 95% confidence interval = 0.01–0.43, P = 0.001). Conclusion: During ultrasonography, a higher degree of the GB wall thickness was found in patients with cholecystitis and cholelithiasis as compared to the control group.